2011
DOI: 10.1177/0310057x1103900319
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Adequacy of Ventilation during Transport of Cardiac Surgery Patients: A Cohort Study

Abstract: Inadequate ventilation of intubated patients during transport from the operating theatre to the intensive care unit with attendant hypercarbia may adversely affect haemodynamics. In a retrospective observational study, we assessed the incidence of inadequate ventilation during transport from the operating theatre to the intensive care unit in 99 consecutive cardiac surgery patients admitted to our university tertiary hospital. Demographic, clinical, arterial blood gas and haemodynamic measurements were made on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(13 reference statements)
1
0
0
Order By: Relevance
“…This finding shows that although there was an increase in the PaCO 2 , it remained within acceptable levels, suggesting that manual ventilation with an MRB at CHBAH may not be injurious as described in some studies. [13,14,21] The results of this study are consistent with studies by Rajasekaram et al [22] and O'Brien et al, [23] who found that there was no clinical difference in the patients who were manually ventilated compared with those who were mechanically ventilated, despite there being a statistically significant change in the PaCO 2 and expired end-tidal CO 2 , respectively.…”
Section: Discussionsupporting
confidence: 90%
“…This finding shows that although there was an increase in the PaCO 2 , it remained within acceptable levels, suggesting that manual ventilation with an MRB at CHBAH may not be injurious as described in some studies. [13,14,21] The results of this study are consistent with studies by Rajasekaram et al [22] and O'Brien et al, [23] who found that there was no clinical difference in the patients who were manually ventilated compared with those who were mechanically ventilated, despite there being a statistically significant change in the PaCO 2 and expired end-tidal CO 2 , respectively.…”
Section: Discussionsupporting
confidence: 90%